Possession (qabd) in contemporary financial transactions: a Shari'ah perspective analysis - Rahman, Md. Habibur; Amanullah, Muhammad (2016)
The possession is one of the significant issues regarding the acquisition of wealth. The conclusion of contracts would not be completed and binding without the possession of respective subject matter. This paper intends to explore the essence of possession and to analyze the appropriate mode of possession in contemporary financial transactions. This is a library-based research and an analytical method has been followed to accomplish this study. The classical references of prominent Schools of Islamic law have been utilized as the primary tools to perform this analysis and exploration. The study finds out that the essence of possession is to relinquish between the merchandise and its rightful beneficiary, so that it can be enjoyed without any interruption. It also explores that the nature of possession would be different according to the nature of the commodity itself. The study posits that in contemporary financial transactions mostly, not the real, but a legal or constructive possession is utilized, and in this regard the custom plays a significant role to determine the proper mode of possession.